The development of automatic internal adjustment system with memory for electronic balances - Intiang, Jittakant; Boonsanit, Sompote; Sirichote, Wichit (Bulletin of Applied Sciences, 2022)
This research is aimed to improve the previous developed automatic internal adjustment system to be included with the memory unit for recording condition (time, temperature, humidity, atmospheric pressure) and number of the adjustment activated. The information is recorded in SD memory card. The sensor system (time, temperature, humidity, atmospheric pressure) and the microcontroller system with SD memory card slot will be assembled together. The C language program is used to control the adjustment system via RS232 port and also command the recording of the condition of automatic adjustment system into the memory unit. When the setting parameters are changed (temperature or time), the adjustment system will be activated and then record the information into the SD memory card. The experiment shows that the electronic balance used in this research is adjusted automatically when temperature or time is changed and also recording the information into the SD memory card.